2017
DOI: 10.1007/s12026-017-8967-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy with interferon-α-induced dendritic cells for chronic HCV infection (the results of pilot clinical trial)

Abstract: The key role of T cells in hepatitis C virus (HCV) elimination and the ability of dendritic cells (DCs) to induce antiviral T cell responses suggest that DC vaccines could be a promising approach in the treatment of chronic HCV infection. The aim of our study was to evaluate, whether immunotherapy with DCs is safe and elicits anti-HCV T cell responses. Ten patients with HCV (genotype 1) were vaccinated with monocyte-derived DCs, generated in the presence of IFN-α (IFN-DCs) and pulsed with recombinant HCV Core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
0
1
Order By: Relevance
“…SARS-CoV-2 peptides are pulsed into an individual's monocytic-DCs and are then used to prime the same individual's T cells, resulting in SARS-CoV-2-specific T cells. These T cells may be cryopreserved or infused into the vulnerable individual as prevention or treatment against COVID-19 [66] , [67] , [68] . …”
Section: Pd-1 and Ctla-4mentioning
confidence: 99%
“…SARS-CoV-2 peptides are pulsed into an individual's monocytic-DCs and are then used to prime the same individual's T cells, resulting in SARS-CoV-2-specific T cells. These T cells may be cryopreserved or infused into the vulnerable individual as prevention or treatment against COVID-19 [66] , [67] , [68] . …”
Section: Pd-1 and Ctla-4mentioning
confidence: 99%
“…It was shown that induction of T cell immune responses by DC vaccination is highly dependent on efficient antigen loading of the DCs [24]. The trials showed that such vaccines did not clear HCV infection in chronic hepatitis C patients despite induction of pronounced T-cell response [25,26]. Thus, the development of MSC vaccines based on genetic and cellular technologies could be one of the most promising strategies to prevent the spread of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Два клинических испытания I / II фаз терапевтических ДК-вакцин для лечения хронического гепатита С перечислены в базах данных ClinicalTrials.gov. В первом использовали аутологичные ДК, сгенерированные из моноцитов в присутствии интерферона α / ГМ-КСФ и пульсированных рекомбинантными белками ВГС Core (1-120) и NS3 (1192-1457) [38,39]. Исследование проводилось в Новосибирске (Российская Федерация), в нем участвовало 10 пациентов в возрасте от 18 до 65 лет.…”
Section: обзоры литературы | Reviewsunclassified